Relationship between blood flow and performance recovery: A randomized, placebo-controlled study - Borne, R.; Hausswirth, C.; Bieuzen, F. (International Journal of Sports Physiology and Performance, 2017)
Purpose: To investigate the effect of different limb blood-flow levels on cycling-performance recovery, blood lactate concentration, and heart rate.